Toward an Advanced Gas Composition Measurement Device for Chemical Reaction Analysis - Gonibala, Fajriansya; Jamilatun, Siti; Amelia, Shinta; Ma’arif, Alfian; Setiawan, Muhammad Haryo (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
The research details the development of a reactor-based monitoring system designed to identify and monitor gases generated within industrial chemical reactors. Consisting of nine MQ and DHT11 sensors, this reactor design allows for simultaneous measurement of temperature and humidity within the sample. Using a sensor array methodology, this research utilizes multiple sensors to collect and process analog signals to improve the accuracy of gas identification within samples. These analog signals obtained from the sensors are processed by an Arduino Mega 2560 microcontroller using the Arduino IDE software. The research, conducted on ten different samples, shows methane (CH4), hydrogen (H2), and alcohol (C2H6O) as the most concentrated gases. Notably, certain samples such as batik waste, honey, Robusta coffee, and sambal have a significant impact on methane gas concentrations. In addition, substances such as Robusta Coffee, Sprite, Syrup, and Oyster Sauce have a significant effect on hydrogen gas concentrations, while Robusta Coffee, Sambal, Arabica Coffee, and Pepper have a significant effect on alcohol gas concentrations. In addition, of the nine MQ sensors used, the MQ3, MQ4, and MQ8 are particularly effective at detecting alcohol, methane, and hydrogen gases, respectively, in the samples tested.